TRANSFORMASI PERAN STRATEGI PEMASARAN DALAM MEWUJUDKAN MINAT BELI - Jubery Marwan (KELOLA: Jurnal Ilmiah Manajemen, 2021)
The transformation of marketing role strategy through social media is very decisive. This technology raises the views and mindset of society radically, whereas the society is very dependent on the technology used. On the other way, producers have their own views on the involvement of social media in influencing people's purchase intentionin possible ways. Through the role of public figures or celebrities, promotion through social media can increase consumer purchase intention. This study aims to analyze the transformation of the role of marketing strategy in realizing consumer purchase intention. The sampling method used quantitative methods with a sample of 98 culinary tourism doer. Where the entire population is used as a sample.  The results of the analysis show there is an influence of marketing strategy on purchase intentionthrough celebrity endorsement variable.